Implication of Career Theories and Psychological Empowerment on Organizational Commitment: take Moderating Effect of Brand Image into Consideration (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the knowledge economy period arrives, talent resource plays an important role increasingly [1]. Despite the fact that the latest technology, innovative marketing and manufacturing process can all be replicated, organizations with more committed and loyal innovative employees will be the winner [2]. Apparently, organizational commitment is an important factor to retain and motivate talent resource, which is a key factor for business success, especially for e-commerce industry. The research verfiy multi-dimensionality of employees’ fit effects on organizational commitment, where has received considerable empirical and theoretical attention in the scientific literature recently. The purpose of this study was to explore more factors that are able to contribute to increase employees’ organizational commitment. This paper described and designed to investigate how inside and outside environments effect on employees’ organizational commitment, where psychological empowerment plays mechanism effect, while taking brand reputation effect into consideration. In order to verified proposed effects on organizational commitment, Ordinary Least Square (OLS) regression was used to analysis 428 participants' feeling extent from e-commerce industry in China through a web-based questionnaire. The results support most of the hypotheses, but the opposite moderating effect of brand image, and control variable 996 working schedule affect almost all the relationships negatively. Even though brand image able to motivate talent employees' passion, but the amount of workload was set above than average and cause working pressure that reduce passion. Due to the realistic research limitations, the extent of organizational commitment could be influenced differently based on organizations' culture factors, which should be explored in subsequent studies. The angle of cultural-based is suggested to add into the proposed framework in future studies to exam the interrelationship between employees’ social identity and their psychological contracts from different culture backgrounds. Additionally, social factors also should be explored and examined in subsequent studies.